2022
DOI: 10.1109/jstars.2022.3200147
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Road Pothole Mapping Based on Vibration Analysis in Smart City

Abstract: Vehicle-road collaboration is inseparable for smart cities, and the potholes detection is an essential direction in vehicleroad collaboration. With the development of artificial surface observation technology and surveying technology, road potholes detection accuracy has improved in recent years. However, the legacy detection methods do not have the ease of service and realtime observation capability, and thus the potholes in the road cannot be mapped in time. To solve this key issue, we proposed a reflectomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, the detection range based on computer vision is the entire visual field of the moving vehicle, and the detection results are also not affected by the speed of the vehicle. Chen et al [14] proposed a reflectometry method, to realize real-time potholes observation, with vibration signals analysis and spatio-temporal trajectory fusion. Akshatha et al [38] used a cloud-based collaborative approach, to fuse the results of acceleration-based detection and vision-data-based detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the detection range based on computer vision is the entire visual field of the moving vehicle, and the detection results are also not affected by the speed of the vehicle. Chen et al [14] proposed a reflectometry method, to realize real-time potholes observation, with vibration signals analysis and spatio-temporal trajectory fusion. Akshatha et al [38] used a cloud-based collaborative approach, to fuse the results of acceleration-based detection and vision-data-based detection.…”
Section: Related Workmentioning
confidence: 99%
“…To meet current pavement maintenance needs, detecting road anomalies with high spatial and temporal coverage has been widely researched. The vibration of the vehicle is the most obvious response to the potholes on the road, and it has been demonstrated that road anomalies can be detected by establishing a relationship between some vibration signatures and road surface characteristics [7,[13][14][15]. For example, Andren [15] proposed that a road roughness spectrum could be derived from the vehicle vibration spectral density.…”
Section: Introductionmentioning
confidence: 99%
“…Modern cities are witnessing a rapid transformation with the integration of advanced technologies, giving rise to the concept of smart cities [1]. These cities leverage cutting-edge infrastructure, digital connectivity, and intelligent systems to enhance the quality of life for their residents [2,3]. The deployment of smart city facilities enables efficient management of resources, optimized transportation systems, and improved public services [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In many vehicles, the engine is positioned near the footrest area, and any imbalance in the engine can lead to the propagation of vibrations to the footrest. Engine imbalances occur due to manufacturing defects, wear and tear, uneven power delivery and the resultant vibrations of reciprocating parts [5,6].…”
Section: Introductionmentioning
confidence: 99%